Similar Trends, Different Agendas: Religious Instruction in Public Schools in Indonesia, Malaysia and Singapore - Sulaiman Mappiasse (Journal of Islamic Education Policy, 2016)
This article argues that national and global events that led to the recent revival of religious education has not altered the nature of the existing arrangement of religious instruction in public schools in Indonesia, Malaysia, and Singapore. Competitive internationalization arena, however, has converged the function of religious education in these countries. It examines how religious instruction in public schools in these ASEAN countries has been transformed in accordance to the emerging demand for global competitiveness. In Indonesia, although the political and economic reform has unsettled the existing structure of the relationship between state and people, the segregated model of religious education classes following religious lines remains in effect. Similarly, in Malaysia, education reform that has been carried out since the early 1990s has not transformed the initial arrangement of religious education. It is still delivered in a way that serves the historical privilege of the Malay ethnic group. Finally, in Singapore, although religious education once gained public popularity, it was only for a short time. The peculiar national agendas of development in each country is argued to be the main determinant of the existing religious education arrangement. Therefore, forces of internationalization arena can only influence the existing state of religious education in a way that serves this national peculiarity.